Labor Share Trends in Three Baltic Countries: Literature Review and Empirical Evidence - Razgūnė, Aušra; Lazutka, Romas (Ekonomika, 2015)
Long-term stability of relative shares of production factors – labor and capital – was an implied fact for a long time. However, recently empirical data have become available, and several authors have presented a conclusive evidence showing a worldwide decline in labor share, which is especially manifested in Continental Europe.Despite the recent scientific interest in the stability of labor share, the trend analysis for small open economies such as the Baltic countries is very limited in the scientific literature. Therefore, this article aims at analyzing theoretical literature and empirical evidences on the changes in functional income distribution with the focus on the Baltic countries while also providing interpretations of the possible causes for this shift. Authors primarily focus on labor share trends in Lithuania, Latvia, and Estonia, while stressing the importance of the correct measurement of this indicator.
Keywords: labor share; Baltic countries; small open economies; functional income distribution